Key Aspects of Finance: From Financial Management to Capital Markets - Anam, Moh Saiful (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This article presents a comprehensive literature review on various aspects of finance. The main focus of this article is on financial management and capital markets. The goal is to provide a better understanding of theory, practice and recent developments in finance. This article contains a review of various theoretical sources and relevant empirical research.